Output Drops and the Shocks That Matter - Mauro, Paolo (IMF Working Papers; Working Paper ;, 2006)
Output drops are usually associated with major disruption for the residents of affected countries, both directly and often through ensuing, prolonged growth slowdowns. Using a century of data, we document that output drops are more frequent in countries at a lower stage of economic development. We then turn to a more in-depth analysis of the post-1970 era, examining output drops in a large panel of countries, and systematically relating them to a variety of shocks. We compute the expected cost of each type of shock as a function of the shock's frequency, the likelihood that the shock will be associated with a drop in output, and the size of the output drop. The largest costs are associated with external financial shocks (notably, sudden stops in financial flows) for emerging markets, and with real external shocks (in particular, terms-of-trade shocks) for developing countries.